2009
DOI: 10.1111/j.1748-5827.2009.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omeprazole on oesophageal pH in dogs during anaesthesia

Abstract: This study suggests that the preoperative administration of omeprazole is effective in reducing the incidence of gastro-oesophageal reflux during anaesthesia in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 32 publications
2
43
1
13
Order By: Relevance
“…Gastroesophageal reflux was detected in 13.3% of the anesthetized dogs in the present study, with this incidence being lower than that observed in other studies with percentages varying from 46 to 60% (Wilson et al 2005(Wilson et al , 2006aPanti et al 2009). All these studies have in common the administration of morphine as part of the pre-anesthetic medication; this seems reasonable when one takes into consideration the finding that morphine reduces EGS tone (Hall et al 1975).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Gastroesophageal reflux was detected in 13.3% of the anesthetized dogs in the present study, with this incidence being lower than that observed in other studies with percentages varying from 46 to 60% (Wilson et al 2005(Wilson et al , 2006aPanti et al 2009). All these studies have in common the administration of morphine as part of the pre-anesthetic medication; this seems reasonable when one takes into consideration the finding that morphine reduces EGS tone (Hall et al 1975).…”
Section: Discussioncontrasting
confidence: 82%
“…This technique allows to identify reflux episodes not visualized as regurgitation, as well as to determine some anesthetic agents that predispose to reflux (Galatos and Raptopoulos 1995a, b;Raptopoulos and Galatos 1997;Wilson et al 2005Wilson et al , 2006aWilson et al , b, 2007Anagnostou et al 2009;Panti et al 2009). It has also allowed to determine that the incidence of GER episodes varies between 4.8% (Anagnostou et al 2009) and 60% (Wilson et al 2005), being influenced by several factors, such as age, type of surgical procedure (Galatos and Raptopoulos 1995a), duration of pre-operative fasting, and drugs used for pre-anesthetic medication (Galatos and Raptopoulos 1995b), induction (Raptopoulos and Galatos 1997) and maintenance (Hashim et al 1995;Wilson et al 2006a) of anesthesia.…”
Section: Introductionmentioning
confidence: 98%
“…Studies evaluating GER in anesthetized humans and dogs have focused on the use of prokinetics and medications to reduce gastric acidity to prevent reflux (Wilson et al ., 2006b;Panti et al ., 2009;Favarato et al ., 2012). In humans, it is also known that drugs that decrease hydrochloric acid production in the stomach, such as ranitidine and omeprazole increase pH and gastric fluids during surgery and therefore decrease the risk of developing Mendelson's syndrome (Grümberg, 2003;Moro, 2004).…”
Section: Preventing Ger During Anesthesiamentioning
confidence: 99%
“…Na medicina veterinária, inúmeras pesquisas utilizaram a pHmetria esofágica com a finalidade de avaliar a incidência de episódios de RGE durante procedimentos anestésicos. Essa técnica tornou possível o reconhecimento daqueles animais que apresentavam refluxo não identificado visualmente como regurgitação, bem como possibilitou identificar alguns agentes anestésicos que predispõem ao quadro (GALATOS & RAPTOPOULOS, 1995a,b;RAPTOPOULOS & GALATOS, 1997;WILSON et al, 2005, 2006a,b, 2007, ANAGNOSTOU et al, 2009PANTI et al, 2009).…”
Section: Métodos De Diagnóstico Dos Episódios De Refluxo Gastroesofágunclassified